TRAINING ON AMBON BANANA FRUIT RIPENING PROCESSING IN BANANA FRUIT SELLERS IN TAWANGMANGU - Setiawan, Ari; Indriyani; Azmi, Yudia; Amilia, Euis; Haumahu, Sara; kesaulya, Irma; Marthina , Alfonsina; A. B Mamesah, Juliaeta; A. Uneputty, Prulley; Fauzi, Fitriya (SMARTINDO, 2025)
Banana is a climacteric fruit that continues to ripen after harvesting, and the ripening process plays a crucial role in determining its market value, taste, and consumer safety. In Tawangmangu, a highland region of Central Java, many banana fruit sellers still employ traditional and unsafe methods for ripening, including the use of non-food-grade chemicals. This community service program aimed to enhance the knowledge and practices of 10 local banana sellers by providing participatory training on natural and safe ripening techniques, with a focus on Ambon bananas (Musa paradisiaca var. sapientum). The training combined theoretical education with hands-on practice in using ethylene-based and hygienic ripening methods. Pre- and post-test evaluations revealed a significant increase in participants’ understanding of postharvest physiology and food safety. Furthermore, 80% of the sellers demonstrated the ability to construct and apply low-cost ripening chambers using local materials, and reported reduced fruit spoilage, improved customer satisfaction, and increased marketability. The program successfully bridged the knowledge gap and introduced a practical, low-resource solution aligned with sustainable development goals. This model has the potential to be replicated in other rural agricultural markets to improve food safety and support local economic empowerment.